Characterizing solute budgets of a tropical Andean páramo ecosystem - Arízaga Idrovo, Viviana (2022)
Monitoring solute fluxes in water quality studies is essential to reveal potential ecosystem disturbances, and is particularly important in Andean headwater catchments as they are the main sources of water for downstream populations. However, such studies have mainly focused on organic matter and nutrients, disregarding other solutes that can threaten water quality (e.g. arsenic, lead, calcium or magnesium). Additionally, routine low-resolution (weekly or monthly) sampling schemes may overlook important solute dynamics. Therefore, we collected water samples every four hours for the analysis of twenty-four solutes in a pristine tropical Andean páramo catchment. Solute fluxes were calculated using five different methods. The 4-hourly data set was filtered to test for an optimum sampling frequency without compromising export rates. Based on the available 4-hourly data, the results showed that the interpolation export method was best suited, due to a weak correlation with discharges. Of the twenty-four solutes analyzed, Dissolved Organic Carbon (DOC), Total Nitrogen bound (TNb), Si, Ca, Mg, K, and Na presented the highest input rates (with DOC = 4.167E+08 mEq km−2 yr−1 and Si = 1.729E+07 mEq km−2 yr−1) and export rates (with DOC = 2.686E+08 mEq km−2 yr−1 and Si = 2.953E+08 mEq km−2 yr−1). Moreover, DOC, TNb, NH4-N, NO2-N, NO3-N, PO4, Al, B, Cu, Fe, Zn, As, Cd, Cr, Pb, and V presented more input than export, while Ca, K, Mg, Na, Rb, Si, Sr, and Ba presented more export than input (geogenic sources). Filtered sampling frequencies demonstrated that a minimum of daily grab samples would be required to obtain reliable export rates with differences consistently below 10%, when compared to the 4-hourly solute export. These findings can be particularly useful for the implementation of long-term monitoring programs at low cost, and they provide high-quality information, for the first time, on biogeochemical budgets in a pristine páramo catchment.